VL

a) 2x+ 3x - 5

b) 16x - 5x- 3

c) x+ 4x + 3

d) x- 4x - 5

e) 16x - 5x2 - 3

 

TH
11 tháng 12 2016 lúc 15:09

a) 2x3 + 3x - 5

= 2x3 - 2x + 5x - 5

= (2x3 - 2x) + (5x - 5)

= 2x(x2-1) + 5(x-1)

= 2x(x+1)(x-1) + 5(x-1)

= (2x2+2x)(x-1) + 5(x-1)

= (x-1)(2x2+2x+5)

Bình luận (0)
NG
11 tháng 12 2016 lúc 7:52

b) 16x - 5x^2 - 3 = - 5^2 + 16x - 3 = -5^2+15x +x - 3 = 5x(3-x) - (3-x) = (3-x)(5x-1);

c) x^2 +4x +3 = x^2 +x + 3x +3 = x(x+1) +3(x+1) = (x+3)(x+1);

d) x^2 -4x -5 = x^2 + x - 5x - 5 = x(x+1) -5 (x+1) = (x-5)(x+1)

e) 16x - 5x^2 - 3 => tương tự câu b 

Bình luận (0)